Fence-Wall diplomacy is a factor for boundary security - I. S. Zonn; S. S. Zhiltsov (Проблемы постсоветского пространства, 2018)
The recent decades have witnessed sweeping changes in the modern global policy and international relations: some countries reinforce their geopolitical positions and economic capacity, while others lose their leading role. However, all states are united in their endeavor to use new mechanisms in asserting their foreign policy issues or make use of the tools that have been developed by some countries through centuries.One of the popular tools to ensure security of the state borders which have been on great demand in the last several decades is building of protective structures on the borders between countries. And about 50 countries have already obtained certain experience in this area applying high technologies and most advanced engineering solutions in implementation of such projects. Such changed approaches to pursuance of foreign policy objectives may be associated with diffusion movement of people caused by military, political and ethnoreligious conflicts, food shortage, climate changes, growing terrorism, crime, corruption, etc.The driving motive here was and still remains the protection of national security and economic interests, curbing the illegal migration, supply of arms and drugs, transboundary terrorism. Construction of protective walls, barriers and fences reflects the level of political relationships among the countries and the level of their economic capabilities with the help of which the states are seeking to stop completely, to revise or drastically restrict bilateral relations.It is not an easy task to assess efficiency of the constructed walls and barriers, and the more so in the face of complex issues existing in bilateral relations. The experience of some countries in implementation of major protection-and-defense projects has shown that they succeed in decreasing the illegal migrant flow, penetration of terrorists, arresting the arms and drugs circulation. However, in general, these efforts within the frame of bilateral relations are a hindrance to development of cooperation between the states reflecting at the same time their inability to settle the arising contradictions on the basis of the international law.